2015
DOI: 10.1073/pnas.1316781112
|View full text |Cite
|
Sign up to set email alerts
|

Solar electricity supply isolines of generation capacity and storage

Abstract: The recent sharp drop in the cost of photovoltaic (PV) electricity generation accompanied by globally rapidly increasing investment in PV plants calls for new planning and management tools for large-scale distributed solar networks. Of major importance are methods to overcome intermittency of solar electricity, i.e., to provide dispatchable electricity at minimal costs. We find that pairs of electricity generation capacity G and storage S that give dispatchable electricity and are minimal with respect to S for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…The recent sharp drop in the cost of generating electricity using PV has triggered an increasing global demand and rapid investment in PV power plants (Grossmann et al, 2015) regardless of the intermittence and seasonal variability of solar energy which appears to be the main obstacle impeding its dependability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent sharp drop in the cost of generating electricity using PV has triggered an increasing global demand and rapid investment in PV power plants (Grossmann et al, 2015) regardless of the intermittence and seasonal variability of solar energy which appears to be the main obstacle impeding its dependability.…”
Section: Introductionmentioning
confidence: 99%
“…Several research studies have been done on photovoltaic in many countries owing to its electricity technology, which has become the fastest growing electricity technology (Grossmann et al, 2015) within the last few decades. Harder and Gibson (2011) studied the cost and benefits (financial feasibility) of large-scale solar PV power production in Abu Dhabi, United Arab Emirates using RETScreen modeling software to predict energy production and greenhouse gas emissions reductions.…”
Section: Introductionmentioning
confidence: 99%
“…This illustrates the fact that onshore wind power in many cases is the most cost-effective technology, but it is limited due to land constraints in the low land availability scenarios. The battery use, too, is higher in the default cases (S and C) with higher share of solar PV 9 . The reduced battery use for the high land availability cases (S-Hland and C-Hland) may be expected since batteries are primarily a short-term storage technology, with a natural synergy with the regular day/night cycles of solar PV.…”
Section: Electricity Supply MIXmentioning
confidence: 94%
“…Some researchers showed that the renewable energy interconnections between the North American countries would be cost-effective41 and environment-friendly 35,36,43. They also contend that expanding the existing interconnected grid would further decrease the need for excess electricity generation and storage 44. Therefore, numerous studies in the relevant literature suggest increasing the level of electricity integration between Canada and the US 35,40,45.…”
Section: The Role Of the Institutions And International Agreements In Regional Electricity Trade: Selected Examples From The Worldmentioning
confidence: 99%